Characteristics and Outcomes of Coronavirus Disease- 2019 Among Pregnant Women in Saudi Arabia; a Retrospective Study - Abdelmola A; Albasheer O; Kariri AA; Akkam FM; Hakami RA; Essa SA; Jali FM (International Journal of Women's Health, 2024)
Amani Abdelmola,1 Osama Albasheer,1 Atyaf A Kariri,2 Fatimah M Akkam,2 Rafeef A Hakami,2 Shahd A Essa,2 Fawziah M Jali2 1Department of Family and Community Medicine, Jazan University, Jazan, Saudi Arabia; 2Faculty of Medicine, Jazan University, Jazan, Saudi ArabiaCorrespondence: Osama Albasheer, Department of Family and Community Medicine, Faculty of Medicine, Jazan University, Jazan, 45142, Saudi Arabia, Tel +966536827923, Email oalbasheer@jazanu.edu.saBackground: Pregnancy-related coronavirus disease 2019 infection ranges from asymptomatic to very serious illness. This study aimed to determine the impact of the COVID-19 infection on pregnant women in the Jazan region of Saudi Arabia.Methods: Retrospective observational study of women who had COVID-19 positive test in pregnancy admitted in King Fahd Hospital, Abu Arish General Hospital, and Sabya General Hospital, Jazan, Saudi Arabia during the period between March 2020 and March 2022. Data were extracted from the patient’s records. Frequency and percentage distributions were calculated for categorical variables. Descriptive studies and regression analysis were conducted to evaluate the association between selected variables and pregnancy outcomes.Results: Of the 33 pregnant women with confirmed infection, the majority were in their second and third trimester, with approximately 42.4% requiring intensive care unit (ICU) admission and oxygen therapy. The most prevalent symptoms were high respiratory rate and low blood pressure, often accompanied by fever, cough, and shortness of breath. Live births resulted in 54.5% of the cases, while two maternal deaths were reported. Significant associations were found between the need for non-invasive ventilation and timing of infection (p = 0.026), the mode of delivery and timing of infection (p = 0.036), and the mode of delivery and body mass index (BMI) (p = 0.007).Conclusion: COVID-19 poses significant risks to pregnant women, particularly in the third trimester, and emphasized the importance of early identification of high-risk pregnancies, strategic planning, and enhanced monitoring during antenatal care.Keywords: COVID-19, pregnant women, maternal outcomes, SARS-CoV-2, Jazan